2019
DOI: 10.1111/jpc.14692
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and aetiology of serious viral infections in young febrile infants

Abstract: Aim: While the incidence and aetiology of serious bacterial infections among febrile infants younger than 90 days old are well studied, those concerning viral infection are not. There are severe life-threatening viral infections requiring immediate intense therapy. The objective of the study is to describe the incidence and aetiology of serious viral infections (SVI) among young febrile infants. Methods: A retrospective audit was performed covering all the febrile infants younger than 90 days old admitted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…RSV infections account for a majority of outpatient and inpatient cases of children with respiratory symptoms in Japan [11,105]. RSV notifications have increased in Japan; however, since late 2011, the interpretation of trends has been challenging owing to a suspected increase in the testing frequency and the expansion of the insurance coverage for RSV testing to include certain outpatients [45].…”
Section: Discussionmentioning
confidence: 99%
“…RSV infections account for a majority of outpatient and inpatient cases of children with respiratory symptoms in Japan [11,105]. RSV notifications have increased in Japan; however, since late 2011, the interpretation of trends has been challenging owing to a suspected increase in the testing frequency and the expansion of the insurance coverage for RSV testing to include certain outpatients [45].…”
Section: Discussionmentioning
confidence: 99%
“…There were approximately 38,000 annual pediatric visits to the ED of the hospital. While the initial patient management is usually provided by pediatric or emergency medicine residents and pediatric emergency medicine fellows, board-certificated emergency medicine physicians or pediatricians supervise patient care [ 15 , 16 ]. Patients with sepsis or suspected sepsis were treated based on the institutional protocol by following the International Pediatric Sepsis Consensus Conference (2005) [ 17 ] and Surviving Sepsis Campaign: International Guidelines for Management of Sepsis and Septic Shock (2012) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…We defined a serious infection in the following manner by applying the definition used in previous studies that covers both bacterial and viral infections [4,21,22].…”
Section: Definitionmentioning
confidence: 99%
“…Diagnosing viral infections was emphasized less due to the self-limiting clinical course of most viral infections. However, recent studies have shown the importance of diagnosing viral infections in the emergency department (ED) due to the fact that several types of viral infection can cause respiratory failure, septic shock, or central nervous system dysfunction requiring intensive care, possibly resulting in unfavorable outcomes in young infants [3][4][5][6]. This has led some researchers to argue for the need to diagnose viral infections in infants [7][8][9].…”
Section: Introductionmentioning
confidence: 99%